Identification of risk categories for in pancreaticoduodenectomy based on diagnosis. Issue 5 (May 2015) - Shubert, Christopher R.; Kendrick, Michael L.; Thomsen, Kristine M.; Farnell, Michael B.; Habermann, Elizabeth B.
Abstract: Background: Studies of pancreaticoduodenectomy (PD) frequently overlook diagnosis as a variable when evaluating postoperative outcomes or generically group patients according to whether they have 'benign' or 'malignant' disease. Large multicentre studies comparing postoperative outcomes in PD stratified by diagnosis are lacking. The present study was conducted to verify the hypothesis that postoperative morbidity and length of stay (LoS) following PD vary by diagnosis and that patients may be grouped into low- and high-risk categories. Methods: The database of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) was reviewed for all PDs performed during 2005–2011. Diagnoses were identified using ICD-9 codes and grouped based on the incidence of major morbidity. Univariate and multivariate analyses were utilized to assess the impact of diagnosis on PD outcomes. Results: Of 5537 patients, those with pancreas cancer ( n = 3173) and chronic pancreatitis ( n = 485) experienced similar incidences of major morbidity ( P = 0.95) and were grouped as having low-risk diagnoses. Patients with bile duct and ampullary ( n = 1181), duodenal ( n = 558) and neuroendocrine ( n = 140) disease experienced similar levels of major morbidity ( P = 0.78) and were grouped as having high-risk diagnoses. A high-risk diagnosis was identified as an independent risk factor for a prolonged LoS [odds ratio (OR) 1.67], organ space infection (OR 2.57), sepsis or septic shock (OR 1.83), and major morbidity (OR 1.70). Diagnosis did not predict readmission. Conclusions: The high-risk diagnosis is independently associated with postoperative morbidity and prolonged LoS. Patients with PD should be stratified by diagnosis to more accurately reflect their risk for postoperative complications and the complexity of care they will require.